Autophagy-dependent ferroptosis in kidney disease - Yang, Yuanting; Cheng, Jiayi; Lin, Qisheng; Ni, Zhaohui (Frontiers in Medicine, 2023)
Ferroptosis is a new type of cell death caused by the lack of glutathione peroxidase 4 (GPX4) and the imbalance of cellular redox. It is characterized by the accumulation of lipid peroxides on cell membranes. Multiple regulatory pathways of ferroptosis include the GPX4, glutamate-cystine antiporter (System Xc–), lipid metabolism, and iron metabolism pathways. Recent studies have reported that autophagy-dependent ferroptosis (ferroptosis meditated by ferritinophagy, lipophagy, and clockophagy) plays a significant role in the occurrence of several diseases, including diseases affecting the nerves, liver, lungs, and kidneys. This review provides an overview of research progress made on autophagy-dependent ferroptosis in kidney diseases.